Right Brain Empowerment in the Learning Process within the Classroom through the Hypnotic Language Transformation Pattern - Nurtaqwa Amin (Tamaddun Life, 2019)
The language approach pattern is one of the most important strategies in the process of transforming learning material in the classroom, because a learning material can be accepted and understood well and is easier for learners to rely heavily on the techniques of using spoken language in transferring knowledge. Based on this, this study uses a hypnotic language pattern approach (transformation pattern "HL to students. Therefore, the problem in this study is how the form and effectiveness of the" HL "transformation approach pattern in classroom learning interactions. reveals the achievement of learning effectiveness through the hypnotic language pattern transformation approach. The results are expected to make a positive contribution to the development of learning methods and strategies and the development of linguistics in using the "HL" (persuasive) transformation pattern which is one of the strategic techniques in empowering the right brain so that students It is easier to understand and enjoy following the learning material. Thus the learning strategy is considered effective. Evidence of effectiveness in learning is shown by research results with a percentage of 100 percent / modules / teaching materials "HLP" approach in learning.